2007
DOI: 10.1111/j.1741-3737.2006.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Relationship Status in Research on Dating and Mate Selection

Abstract: The relationship status of study participants (e.g., daters, cohabitors, marrieds, or unmarrieds) has implications for understanding dating and mate selection. Procedures used in studies may blur or ignore status distinctions. The authors examined methods used in 791 studies published from 1991 – 2001. Most commonly, status of participants is unspecified, and different statuses are collapsed for analysis. Status of participants is associated with recruitment method, and type (e.g., romantic, friendship) and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Similarly, a review of articles published in the 1990's found that relationship status was not assessed or was collapsed in most samples suggesting that behaviors and affective states do not change over the development of a relationship (Surra, Boettcher-Burke, Cottle, West, & Gray, 2007). As concluded by the authors of the review, we believe that relationship development does play a role in the behaviors and emotions displayed in a romantic relationship.…”
mentioning
confidence: 92%
“…Similarly, a review of articles published in the 1990's found that relationship status was not assessed or was collapsed in most samples suggesting that behaviors and affective states do not change over the development of a relationship (Surra, Boettcher-Burke, Cottle, West, & Gray, 2007). As concluded by the authors of the review, we believe that relationship development does play a role in the behaviors and emotions displayed in a romantic relationship.…”
mentioning
confidence: 92%
“…Previous studies have shown that non-residential partnerships are quite common in societies with a late pattern of marriage and low prevalence of cohabitation, such as Japan (Rallu andKojima 2000, Iwasawa 2004). Living-apart-together among young adults may be more relevant than ever, as individuals spend more of their lifetimes dating and selecting mates than previously (Surra et al 2007) and, once they find a suitable partner, they feel little social and family pressure to "settle down" together in a common dwelling. We will try to elucidate whether the high prevalence of non-residential partnerships among young adults is linked to economic constraints (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study about relationship status recommended that future research clarify relationship language, because language is always evolving (Surra et al 2007).…”
Section: Discussionmentioning
confidence: 98%